2020
DOI: 10.3389/fmicb.2020.01685
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Galectin-9 but Not Osteopontin in HIV and Tuberculosis Infections Indicate Their Roles in Detecting MTB Infection in HIV Infected Individuals

Abstract: Galectin-9 (Gal-9) and osteopontin (OPN) play immunomodulatory roles in tuberculosis and HIV infections. Evaluation of their levels as well as their interplay with different pro-inflammatory cytokines is critical to understand their role in immunopathogenesis of HIV/tuberculosis co-infection considering the complexity of the disease. Plasma levels of these proteins were measured by ELISAs in HIV-negative individuals with pulmonary (n = 21), extrapulmonary (n = 33), and latent tuberculosis (n = 22) and in HIV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Recently, an assay to measure the cleaved form of Gal-9 was developed [ 50 ]. A biomarker analysis conducted in patients with HIV/OI revealed that levels of Tr-Gal-9 markedly reflect the disease severity of the co-infected individuals [ 53 , 96 ]. The Tr-Gal-9 may be generated via cleavage by MMP-9, which has also been proposed to be a non-sputum-based biomarker for differentiating pulmonary TB and extrapulmonary TB [ 97 ].…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…Recently, an assay to measure the cleaved form of Gal-9 was developed [ 50 ]. A biomarker analysis conducted in patients with HIV/OI revealed that levels of Tr-Gal-9 markedly reflect the disease severity of the co-infected individuals [ 53 , 96 ]. The Tr-Gal-9 may be generated via cleavage by MMP-9, which has also been proposed to be a non-sputum-based biomarker for differentiating pulmonary TB and extrapulmonary TB [ 97 ].…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…Ud-OPN and IL-6 levels were higher in patients with severe chest X-ray grade, indicating their association with disease severity, and were positively correlated with each other [114]. The plasma levels of Ud-OPN were significantly higher in patients with severe PTB in which lesions involved four or more zones without cavities or more than three zones with cavities, as compared with those with non-severe PTB (Table 2).…”
Section: Tuberculosis (Tb)mentioning
confidence: 87%
“…Ud-OPN levels were also significantly higher in patients with AIDS/TB and TB [105,106,114]. Although the OPN levels were significantly higher in human immunodeficiency virus (HIV)-negative pulmonary TB (PTB) patients than in those with latent TB, the same trend was not observed in HIV-infected patients, indicating its limitation in detecting TB development in HIV infection [114]. The levels decreased significantly after successful TB treatment, as indicated by clinical improvement or sputum smear conversion, suggesting its potential to monitor the effect of treatment [104,121].…”
Section: Tuberculosis (Tb)mentioning
confidence: 97%
See 2 more Smart Citations